Muscle strength differences in healthy young adults with and without generalized joint hypermobility: a cross-sectional study. Issue 1 (December 2016) - Jindal, Pranay; Narayan, Amitesh; Ganesan, Sailakshami; MacDermid, Joy
Abstract Background Generalized joint hypermobility (GJH), in the absence of symptoms, is a common clinical finding. The joint instability present due to excessive musculoskeletal flexibility in hypermobile joints impairs the external force production during muscle contraction. However, whether GJH is associated with muscle weakness is unclear. This study evaluated differences in upper and lower limb muscle strengths among asymptomatic young adults with and without GJH. Methods One hundred six young adults (53 hypermobile, i.e. 25 male (mean age 22 ± 1.8); 28 female (mean age 21 ± 1.8), and 53 non-hypermobile, i.e. 25 male (mean age 19 ± 1.06); 28 female (mean age 20 ± 1.4) were selected using a cut-off ≥ 4 on Beighton and Horan Joint Mobility Index. Isometric strength of elbow and knee extensors was measured using an isokinetic dynamometer. Independent sample t- tests were done to compare the muscle strengths of hypermobile and non-hypermobile participants. One-way ANCOVA was applied to control the effect of height and body mass on muscle strength. Results Male hypermobile participants had significantly less strength than non-hypermobile males in the right (71.7 Nm, SD = 23.1, vs 97.6 Nm, SD = 47.4, p = 0.006*) and left (74.8 Nm, SD = 24.3, vs 97.7 Nm, SD = 45.5, p = 0.007*) elbow extensors and right knee extensors (188.7 Nm, SD = 83.3, vs 228.3 Nm, SD = 106.7, p = 0.03*). In females, both elbow extensors (right: 51.9 Nm, SD = 16.2 vs 48.8 Nm, SD = 17.8, p = 0.4; left: 48.9 Nm, SD = 17.2, vs 44.7 Nm, SD = 15.1, p = 0.2) and knee extensors (right: 161.3 Nm, SD = 74.9 vs 145.5 Nm, SD = 75.8, p = 0.3; left: 155.2 Nm, SD = 73 vs 124.3 Nm, SD = 69.6, p = 0.07) strength were not statistically different between hypermobile and non-hypermobile participants. Conclusion The findings indicate that male participants with GJH have less isometric muscle strength in both elbow extensors and right knee extensors compared to non-hypermobile male participants. Female hypermobile participants did not show any significant differences in muscle strength compared to non-hypermobile female participants.